Did Perceived Stress Influence Possible Sleep Bruxism and Awake Bruxism in Dentistry Students During COVID-19 Pandemic? A Web-Based Cross-Sectional Study - Smyrna Luiza Ximenes de Souza; Alessandro Leite Cavalcanti (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the influence of perceived stress during the COVID-19 pandemic over awake bruxism (AB) and sleep bruxism (SB).Material and Methods: Observational web-based research carried out in a state in the Brazilian Northeast. The sample was composed of dental students from seven faculties, divided into three groups: beginning (1-4 semesters), middle (5-7), and end (8-10). An online questionnaire was constructed: Socio-demographic, Perceived Stress Scale (PSS-10), Self-reported AB and SB, and COVID-19 Fear Scale. Data were collected from April to June 2021 by sending the questionnaire through WhatsApp®, e-mail, and Instagram®. After bivariate analyses, a multiple logistic regression model was performed to discriminate variables for perceived stress and AB and SB. Hosmer and Lemeshow and chi-square tests were used to check the model's goodness of fit. Results: A total of 391 dental students participated in this research - most women (69.8%), unmarried (69.8%), family income less than three minimum wages (60.9%), self-reported physical activity (63.3%). Perceived stress was low to moderate (72.1%), SB was 39.6%, AB was 49.6%, and low COVID-19 fear was 81.1%. COVID-19 fear (3.03), being female (2.47), and using psychotropic (2.53) increases the chance of being stressed. Perceived stress can predict AB in models 1 (p=0.008) and 4 (p=0.039). There was no significance for perceived stress and SB. Conclusion: Perceived stress during the COVID-19 pandemic influenced awake bruxism.